Comparative effects of energy restriction and resveratrol intake on glycemic control improvement. (20th February 2017) - Milton‐Laskibar, I.; Aguirre, L.; Macarulla, M.T.; Etxeberria, U.; Milagro, F.I.; Martínez, J.A.; Contreras, J.; Portillo, M.P.
Abstract: Resveratrol (RSV) has been proposed as an energy restriction mimetic. This study aimed to compare the effects of RSV and energy restriction on insulin resistance induced by an obesogenic diet. Any additive effect of both treatments was also analyzed. Rats were fed a high‐fat high‐sucrose diet for 6 weeks. They were then distributed in four experimental groups which were either fed a standard control diet (C), or treated with RSV (30 mg/kg/d), or submitted to energy restriction (R, 15%), or treated with RSV and submitted to energy restriction (RR). A glucose tolerance test was performed, and serum glucose, insulin, fructosamine, adiponectin, and leptin concentrations determined. Muscle triacylglycerol content and protein expression of insulin receptor (IRβ), protein kinase B (Akt), Akt substrate of 160 kDa (AS160) and glucose transporter 4 (GLUT‐4) were measured. In RSV rats, fructosamine concentrations were reduced, HOMA‐IR remained unchanged, but glucose tolerance was improved, without changes in phosphorylation of IRβ, Akt, and AS160 or in GLUT‐4 protein expression. Rats under energy restriction showed an improvement in all the markers related to glycemic control, as well as increased phosphorylation of AS160 and protein expression of GLUT‐4. In rats from RR group the results were similar to R group, with the exception of IRβ and Akt phosphorylation, which were increased. In conclusion, mild energy restriction is more efficient than intake of RSV within a standard balanced diet, and acts by means of a different mechanism from that of RSV. No additive effects between RSV and energy restriction were observed. © 2017 BioFactors, 43(3):371–378, 2017